Solid phase morphological diversity of a rare vanadium cubane (V4O16) based metal organic framework - Dey, Chandan; Das, Raja; Poddar, Pankaj; Banerjee, Rahul (Crystal Growth & Design, 2012)
A Cu(II) connected V4O16-cubane based metal organic framework, Cu-2(phen)(2)(V4O8) (PO4)(4) [Cu2V4O16-2D] was synthesized under hydrothermal conditions. This is the first example of transition metal connected V4O16-cubane based MOF. X-ray single crystal data shows the alternate arrangement V4O16-cubane and Cu(phen)(O)(3) square pyramidal unit in two dimensions. These two-dimensional sheets are stacked on top of each other to form a three-dimensional architecture. Cu2V4O16-2D shows two types of solid state morphologies of the same phase, which was confirmed by scanning electron microscopy. It is noteworthy that this type of morphological difference of the solid phase in an extended metal organic hybrid material is rare and has not been perceived in the polyoxovanadate based MOFs literature. Cu2V4O16-2D was further characterized by powder X-ray diffraction (PXRD), thermal gravimetric analysis (TGA), IR-spectroscopy, scanning electron microscopy (SEM), and elemental analysis. We also studied the static magnetic and gas adsorption properties for Cu2V4O16-2D.